Design and characterization of symmetric nucleic acids via molecular dynamics simulations. Issue 4 (April 2017) - Pant, Pradeep; Afshan Shaikh, Saher; Jayaram, B.
Abstract: Asymmetry (5′→3′) associated with each strand of the deoxyribonucleic acid (DNA) is inherent in the sugar‐phosphate backbone connectivity and is essential for replication and transcription. We note that this asymmetry is due to one single chemical bond (C3′ to C2′ ) in each nucleotide unit, and the absence of this bond results in directionally symmetric nucleic acids. We also discovered that creation of an extra chemical bond (C5′ to C2′ ) can lead to a symmetric backbone. Keeping their potential synthetic and therapeutic interest in mind, we designed a few novel symmetric nucleic acids. We investigated their conformational stability and flexibility via detailed all atom explicit solvent 100‐ns long molecular dynamics simulations and compared the resulting structures with that of regular B‐DNA. Quite interestingly, some of the symmetric nucleic acids retain the overall double helical structure indicating their potential for integration in physiological DNA without causing major structural perturbations.